Reliability of Biomarkers of Physiological Stress at Rest and Post-exertional Heat Stress - Snape, Daniel; Wainwright, Barney; Woods, David R; O’Hara, John Paul (International Journal of Sports Medicine, 2022)
The purpose of this study was to assess the reliability of blood biomarkers that can signify exercise-induced heat stress in hot conditions. Fourteen males completed two heat stress tests separated by 5–7 days. Venous blood was drawn pre- and post- heat stress for the concentration of normetanephrine, metanephrine, serum osmolality, copeptin, kidney-injury molecule 1, and neutrophil gelatinase-associated lipocalin. No biomarker, except copeptin, displayed systematic trial order bias (p≥0.05). Normetanephrine, copeptin and neutrophil gelatinase-associated lipocalin presented acceptable reliability (CV range: 0.9–14.3%), while greater variability was present in metanephrine, osmolality and kidney-injury molecule 1 (CV range: 28.6–43.2%). Normetanephrine exhibited the largest increase (p<0.001) in response to heat stress (trial 1=1048±461 pmol. L-1; trial 2=1067±408 pmol. L-1), whilst kidney-injury molecule 1 presented trivial changes (trial 1=–4±20 ng. L-1; trial 2=2 ± 16 ng. L-1, p>0.05). Normetanephrine, copeptin, and neutrophil gelatinase-associated lipocalin demonstrated good reliability and sensitivity to an acute bout of heat stress. These biomarkers may be suitable for application in laboratory and field research to understand the efficacy of interventions that can attenuate the risk of thermal injury whilst exercising in the heat.
Keywords: reliability; heat-stress; endurance; sympathoadrenal; fluid-regulation; kidney-function